Gelenekselci ekole göre din ve modernleşme: René Guénon örneği - Akdoğan, Sinan (My University, 2010)
GELENEKSELCİ EKOLE GÖRE DİN VE MODERNLEŞME: RENÉ GUÉNON ÖRNEĞİ Köklerini on beşinci yüzyıldan sonra Avrupa’da ortaya çıkan Rönesans ve Reform hareketlerinden alan modernleşme süreci, on sekizinci yüzyıl Aydınlanma döneminde, Avrupa’da gerek toplumsal hayatın gerekse diğer kültürel alanların tamamını etkileyen bir olgu haline gelmiştir. On dokuzuncu ve yirminci yüzyıllarda bu hazırlayıcı aşamalardan sonra modernite dönemine girilmiştir. Bundan sonra modernlik, kendi farkındalığını ötekileştirdiği gelenekle elde etmeye çalışmıştır. Modernitenin bu şekilde yadsıdığı gelenek, René Guénon tarafından şimdiye kadar olduğundan çok daha farklı ve derin bir boyutu ifade edecek biçimde yeniden tanımlanmıştır. Biz bu çalışmada Gelenekselci Ekol’ün kurucusu olan Guénon’un din ve modernleşme anlayışını ortaya koymaya çalıştık. Onun ortaya koyduğu geleneğin bu özgün anlamı moderniteyi anlamada önemli bir unsur haline gelmiştir.

RELIGION AND MODERNITY IN TRADITIONALIST SCHOOL: A SAMPLE OF RENÉ GUÉNONModernity process, which takes its origins from the movements of Renaissance and Reform, emerging in Europe after 15th century, has became a phenomenon affecting social and cultural life in 18th century - the Age of Enlightenment-. After this preperatory phases in 19th and 20th century, period of modernity has started. Henceforth, modernity has tried to get its own awareness thanks to tradition which is otherised by it. Tradition ignored by modernity was redefined by René Guénon as an expression of more different and deep dimension up till now. We tried to present the consideration on religion and modernity of Guénon who is founder of Traditionalist School. His explanations about authentic meaning of tradition has became an important element for understanding of modernity.AUTOBIOGRAPHYSinan AkdoğanE-Mail: sinanakdogan@gmail.com / Phone :0530 466 96 75I was born in Çarşamba-the town of Samsun- at July 10, 1983. After the high school graduation, I was registered to the department of Religious Culture and Ethics Teaching in Samsun 19 May Faculty of Theology. I was graduated from this faculty in 2006. At 2007, I was inducted as a Religious Culture and Ethics Teaching teacher in Arnavutköy -town of İstanbul. I was assigned in Kadıköy after working two years in Arnavutköy. I still work in Kadıköy as a teacher.
Keywords: Din Sosyolojisi; Modernleşme